2019
DOI: 10.1002/nau.24054
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and surgical outcomes of ectopic ureters in adults: A case series and literature review

Abstract: Objectives To evaluate functional outcomes of surgery in patients with ectopic ureters diagnosed in adulthood; to review the world literature. Patients and methods Patients were referred over 10 years. Data including surgical history, presenting symptoms, diagnostic modalities, interventions and functional outcomes were collected; and the world literature reviewed. Results 9 women and 1 man had a mean age of 37 (range 20‐58). All women were referred with lifelong leakage. The man was referred with storage LUTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…High resolution MR Urography is valuable in the evaluation of ectopic ureters as well as nonfunctioning renal poles even without contrast because they are frequently filled with T2-hyperintense fluid representing excreted urine [37,41,42]. The dynamic renal scintigraphy is the modality of choice to diagnose Yo-Yo reflux [12,43] which was not available at our Health Centre.…”
Section: Discussionmentioning
confidence: 99%
“…High resolution MR Urography is valuable in the evaluation of ectopic ureters as well as nonfunctioning renal poles even without contrast because they are frequently filled with T2-hyperintense fluid representing excreted urine [37,41,42]. The dynamic renal scintigraphy is the modality of choice to diagnose Yo-Yo reflux [12,43] which was not available at our Health Centre.…”
Section: Discussionmentioning
confidence: 99%
“…Toia et al pointed out the role of ectopic ureter in differential diagnosis of the lifelong urinary incontinence. They recommended MRI as an examination of choice in the diagnostic process and showed that patients with ectopic ureters might require additional treatments in order to achieve continence [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Duplex systems may have a broad spectrum of manifestation including ectopic ureter and continuous urinary leakage [ 8 ]. Although these pathologies are well known and described in pediatric patients, limited cases have been reported in adults until now [ 9 , 10 ]. We describe two cases with ureteral duplication and ureteric enuresis which became symptomatic in adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study over 7 years reported that patients diagnosed with an ectopic ureter ranged in age from 1 to 13 years, with a mean age of 4.5 years [ 3 ]. Notably, the uncommon cases diagnosed in adults suggest that the prevalence of ectopic ureter may be higher [ 4 ]. Patients with ectopic ureter generally present with other malformations of the urinary system, such as a duplex or single collecting system, even with female genital tract anomalies [ 5 ].…”
Section: Introductionmentioning
confidence: 99%